Literature survey on post war marketing strategies for the Conflcit effcetd areas of Sri Lanka - Shivany, S.; Velnampy, T.; Kajendra, K. (My University, 2015)
War is an overwhelming experience, leaving its mark on society, physical structures, legal systems, and almost every aspect of a country’s social, political, economic, and business activities. For redevelopment to be effective, it requires a careful and concerted approach that draws on domestic resources, international donor assistance, and private sector participation, and marketing strategies for improving business success. Countries emerging from conflict typically face multiple challenges in rebuilding homes, schools, factories, banks, communications networks, and other key business infrastructures in the post war /conflict business environment. The currency is weak, human resources diminished, and key institutions seriously impaired, all factors leading to thoughtful, extensive poverty. Therefore, at the post war marketing environment challenge is to develop an integrated approach that will help countries mend their post-conflict wounds and move towards a path of long-term sustainable development in marketing and trade. The conflict between the armed forces of the Government of Sri Lanka and the Liberalized Tiger of Tamil Eelam began in 1983. It is characterized in part by its relative isolation from the rest of the country. Most of the fighting and war-related obliteration has occurred in the eight contested districts of the North and East, while other parts of the country have remained largely free of such direct destruction. In the high conflict areas, the conflict has taken on the character of a civil war, in that non-combatants, or civilians, are drawn in and suffer as a result. The conflict takes place within a highly contested tract of land that is still inhabited in parts. The thirty years of civil war in Sri Lanka, has effected, on Sri Lankan economy, business growth, internal business relationships, market infrastructures, supply chain, market access, local industries, marketing ethics, as well as the international marketing opportunities. The internal war has been ended in May 2009. This end has given many opportunities to Sri Lankan economy, as well as to the conflict effected provinces. New policy frameworks, business strategies, educational reformulation, and social harmony enrichment, business expansion, and infrastructure developments are focused by the government with the help of foreign direct and indirect investment. Marketing environment in the war situation and the post war marketing environment is completely different, local marketers are now struggling to compete with the marketers, who newly entered into the war effected places. Good marketing practices, business ethics had not been followed by the marketers in the war scenario, traditional marketing approaches were only adopted by the marketers. Consumers also weren’t conscious on the business perspectives. They were only concern about their sustainability of alive. But in the post war marketing environment consumers concern with all aspect in marketing. They have experienced and have knowledge on everything in business. The marketers, who adopt the traditional approaches, also struggle to survive in the market. Marketing has been identified as a strategic role rather than, supporting sales, so marketing strategies should be specially concerned in the postwar marketing environment, to support local marketers to survive in the market.